Journalistic representation of women in the reportage of military operations against Boko Haram in Northeast Nigeria - Ndinojuo, Ben-Collins (2021)
The role of women in the reportage of military operations against the Boko Haram insurgents and their portrayal in news reports were investigated in this study. Radical Feminist Theory and Feminist Muted Group Theory were used to elucidate the research. Using content analysis, online editions of four Nigerian newspapers―Daily Trust, Premium Times, The Nation, and Vanguard―from January 2014 to December 2016 were investigated to reveal how women were presented in news reports. Findings produced 185 news stories; women were included in 10 % of the total pictures used. Women made up 8 % of the bylines and 4% of the sources, with 59 % of the women mentioned in the news presented as kidnap and rescued victims. The study found an underrepresentation and misrepresentation of women in news reports, which were attributed to the male-dominated journalism field that preferred using their male sources to the detriment of issues affecting women.